POTENSI TANAMAN OBAT BANONDIT (Biophytum petersianum Klotzsch) SEBAGAI SUMBER PAKAN HIJAUAN DI LEMBAH KEBAR PAPUA BARAT - Sawen, Diana (Pastura, 2014)
Banondit has been known as “Kebar grass” by the people in Papua Kebar valley and also in Indonesia for generations. This study was carried out to know the potential extent of banondit as medical plant and source of forage for livestock. The study lasted for 2 months by using descriptive method with case studies. Local com- munities, the one who get benefit from these species, were used as respondents by using random sampling. The results showed that community utilized banondit as drugs in their life to improve fertility for men and women, to normalize menstrual cycle, and for livestock (Bali cattle, goats, pigs and chicken) which cultivated in this location. Banondit within other forages grew naturally dispersed on pastures at Kebar. Livestock raising system remain extensive with the biological rhythm which has been formed for years. In that case, these animals continually consumed banondit according to their needs.
Keywords: Biophytum petersianum Klotzsch, potensi, hijauan pakan